2009
DOI: 10.1021/ic900912d
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Fluorination of La2CuO4: A Mild “Chimie Douce” Route to Superconducting Oxyfluoride Materials

Abstract: The fluorination of La(2)CuO(4) was achieved for the first time under normal conditions of pressure and temperature (1 MPa and 298 K) via electrochemical insertion in organic fluorinated electrolytes and led to lanthanum oxyfluorides of general formula La(2)CuO(4)F(x). Analyses showed that, underneath a very thin layer of LaF(3) (a few atomic layers), fluorine is effectively inserted in the material's structure. The fluorination strongly modifies the lanthanum environment, whereas very little modification is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 62 publications
1
11
0
Order By: Relevance
“…The other example is the electrochemical fluorination of La2CuO4 in a classic three-electrode configuration using organic fluorinated electrolytes (in liquid state) and gold foil and Pt wire as counter and reference electrodes, respectively. 137 In this work, it was reported that 0.18 fluoride ions had been electrochemically inserted in the vacant interlayers of La2CuO4, resulting in an increase in the parameter c of the cell from 13.141 Å to 13.205 Å. The results were in good agreement with what was found using chemical fluorination methods using F2 gas.…”
Section: Intercalation-based Cathode Materialssupporting
confidence: 86%
“…The other example is the electrochemical fluorination of La2CuO4 in a classic three-electrode configuration using organic fluorinated electrolytes (in liquid state) and gold foil and Pt wire as counter and reference electrodes, respectively. 137 In this work, it was reported that 0.18 fluoride ions had been electrochemically inserted in the vacant interlayers of La2CuO4, resulting in an increase in the parameter c of the cell from 13.141 Å to 13.205 Å. The results were in good agreement with what was found using chemical fluorination methods using F2 gas.…”
Section: Intercalation-based Cathode Materialssupporting
confidence: 86%
“…Compounds with the Ruddlesden–Popper-type structure A n +1 B n O 3 n +1 are known for a variety of functional properties, among them superconductivity and catalytic, ferroelectric, and magnetic , properties. The member with n = 1 (A 2 BX 4 , often referred to as K 2 NiF 4 -type structure) can be understood as being built of alternating layers of perovskite ABX 3 and rock salt AX layers.…”
Section: Introductionmentioning
confidence: 99%
“…4,6 Although conversion materials have been studied for decades the underlying mechanisms of these conversion reactions are still not well understood. [7][8][9] Fluorination reactions to form the electrode materials can be performed by a variety of methods including precipitation from a uorinated solution, reaction with HF, 10 direct reaction with F 2 (g), solid-state reactions with a uorinating agent such as NH 4 F, CuF 2 , ZnF 2 , XeF 2 , AgF 2 or NH 4 HF 2 , 11,12 electrochemical uorination 13 and reaction with poly(vinylidene uoride) (PVDF). 14 Experimental conditions including reaction time, temperature and uorine concentration can be used to control the level of uorine insertion and the homogeneity of the products.…”
Section: Introductionmentioning
confidence: 99%